2011
DOI: 10.1016/j.socscimed.2011.05.025
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the economic impact of pandemic influenza: An application of the computable general equilibrium model to the UK

Abstract: There is concern regarding the impact that a global infectious disease pandemic might have, especially the economic impact in the current financial climate. However, preparedness planning concentrates more upon population health and maintaining a functioning health sector than on the wider economic impact. We developed a single country Computable General Equilibrium model to estimate the economic impact of pandemic influenza (PI) and associated policies. While the context for this development was the United Ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
58
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(59 citation statements)
references
References 21 publications
0
58
0
1
Order By: Relevance
“…A similar study in North Carolina found that 24% of households reported missing work. Prior study has shown through sensitivity analyses that there may be less variability with regards to fluctuations in disease parameters than with policies such as school closure and recommendations to stay home . In fact, CDC policy recommended ill persons to stay home for up to seven days during the H1N1 pandemic.…”
Section: Analysis and Discussionmentioning
confidence: 99%
“…A similar study in North Carolina found that 24% of households reported missing work. Prior study has shown through sensitivity analyses that there may be less variability with regards to fluctuations in disease parameters than with policies such as school closure and recommendations to stay home . In fact, CDC policy recommended ill persons to stay home for up to seven days during the H1N1 pandemic.…”
Section: Analysis and Discussionmentioning
confidence: 99%
“…The integration of economic and epidemic models for pandemic preparedness does not yet appear to have explored all possible model combinations, with a large scope for modelling innovation. For instance, although advanced economic models such as CGE models have been applied to influenza pandemics and were able to capture the effects of job absenteeism or deaths on the affected sectors of various economies [66,78,79], our review did not identify any study that combined such models with dynamic epidemic models in a way that both models feedback on to each other. Not allowing feedback is reasonable if job absenteeism can be approximated as a sudden shock to the production systemsthough in reality the shock might be progressive or present several peaks-or if feedback from the economy into the epidemic is not expected.…”
Section: Economic Aspectsmentioning
confidence: 99%
“…In our review, the inclusion of individuals' behaviour was more common among simulation models although, instead of basing behaviour representation on game or microeconomic theory, it was usually based on simple rules and assumptions. Different kinds of behaviours were considered in several models, including voluntary isolation, increased social distancing once infected, and preventive behaviour [33,42,66,74,79,[82][83][84][85]. The inclusion of behaviour can lead to substantially different conclusions.…”
Section: Individual Behaviourmentioning
confidence: 99%
“…It warrants the inclusion of at least part of the broader impact vaccines have been suggested to generate. 8,11 A few countries already stimulate the societal perspective to be used in standard economic assessment of new interventions, and for vaccines in particular. Among them are the Netherlands, Sweden, Portugal and France but the results will be highly influenced by the way social security systems are organized in a country or whether the utility impact on (all) family members caring for the individuals at risk is taken into account.…”
mentioning
confidence: 99%